Occupations du Paléolithique supérieur dans le sud-est du Bassin parisien - Julien, Michèle; Rieu, Jean-Luc (Documents d'archéologie française, 1999)
Three Upper Palaeolithic sites have been discovered during the construction of the A5 motorway between Melun and Troyes.Marolles-sur-Seine, in the Seine-et-Mame area, is related to the other Magdaleman sites discovered in the Paris basin. The excellent preservation of the finds (silex, animal bones, heated stones) has made possible a palaeoethnological study of this horse hunting site, a type of research rarely possible in a rescue excavation Technological analysis of the lithic from Lailly (Aungnacian), in the Yonne area, and Fontvannes (Perigordian ?), in the Aube area, has revealed the production techniques for three kinds of artefacts blades, flakes and bladelets. These two sites increase the importance of the Vanne valley in the understanding of occupation of the south east of the Paris basin.Following the publication about the Middle Palaeolithic sites of the Sens area (dAf number 47), this volume renews the study of early Prehistory in this region